2020
DOI: 10.1038/s41467-020-19022-2
|View full text |Cite
|
Sign up to set email alerts
|

Dietary diversity and evolution of the earliest flying vertebrates revealed by dental microwear texture analysis

Abstract: Pterosaurs, the first vertebrates to evolve active flight, lived between 210 and 66 million years ago. They were important components of Mesozoic ecosystems, and reconstructing pterosaur diets is vital for understanding their origins, their roles within Mesozoic food webs and the impact of other flying vertebrates (i.e. birds) on their evolution. However, pterosaur dietary hypotheses are poorly constrained as most rely on morphological-functional analogies. Here we constrain the diets of 17 pterosaur genera by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 62 publications
1
32
0
Order By: Relevance
“…This conclusion is also supported by a recent DMTA study on reptiles 29 , which exhibit significant overlap with sharks in the parameter trends correlating with 'harder' diets. Of the parameters correlating with increasing PC 1 values in sharks, parameters correlated with increasing dietary 'hardness' in reptiles include those capturing aspects of texture height (Sa, Sq, S5z), the number of peaks (Spk), and the depth, void volume and material volume of the core (Sk, Vvc, Vmc).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…This conclusion is also supported by a recent DMTA study on reptiles 29 , which exhibit significant overlap with sharks in the parameter trends correlating with 'harder' diets. Of the parameters correlating with increasing PC 1 values in sharks, parameters correlated with increasing dietary 'hardness' in reptiles include those capturing aspects of texture height (Sa, Sq, S5z), the number of peaks (Spk), and the depth, void volume and material volume of the core (Sk, Vvc, Vmc).…”
Section: Discussionsupporting
confidence: 67%
“…The approach offers several advantages: it provides direct evidence of tooth use that is independent of functional analyses based on morphology of the jaws and teeth; dietary signals accumulate over longer timescales than stomach contents, avoiding the 'snapshot' problem 5,24 ; it can detect subtle dietary differences between individuals and populations, even when sample sizes are small 24,26,27 . The method is also highly applicable to fossils 19,28,29 and to specimens that are not amenable to stomach contents analysis, and in contrast to stable isotope analysis it provides evidence of the nature of food rather than the relative trophic level at which an organism is feeding.…”
mentioning
confidence: 99%
“…Diagrams not to scale. The A. mississippiensis mandible was redrawn from [ 45 ] under a Creative Commons Attribution open-access license and the V. rudicollis mandible was redrawn from [ 27 ] under a Creative Commons Attribution 4.0 International License ( ). …”
Section: Methodsmentioning
confidence: 99%
“…The known relationships between microwear texture and diet in extant reptiles therefore provides us with a robust multivariate framework with which to quantitatively test and constrain phytosaur dietary hypotheses using DMTA (Bestwick et al . 2020a).…”
mentioning
confidence: 99%
“…While no direct morphological or ecological comparisons have been made between phytosaurs and varanids, previous DMTA of reptiles has shown that microwear texture differences are more strongly linked to dietary differences than they are to tooth morphology or phylogeny (Bestwick et al . 2019, 2020a; Winkler et al . 2019).…”
mentioning
confidence: 99%